Bioethics of sport and its place in the philosophy of sport - Škerbić, Matija Mato (Array, 2020)
In the Routledge Handbook of the Philosophy of Sport (McNamee, Morgan, 2015) for the first time Bioethics of Sport (BES) was included, and therefore officially acknowledged, as a separate field within the Philosophy of Sport. Starting from that fact, I will raise three issues. Firstly, I will propose the definition for the (new) sub-discipline, briefly present its short history, and indicate the connection to the Bioethics as such. Secondly, I will point out the BES thematic scope in the past and present, and show how and why it is too narrow, insufficient and not comprehensive enough. In that regard, relying on Fritz Jahr’s understanding of Bioethics, I will propose the widening of the current scope, and demonstrate that many of the topics were already present in the discourse of the philosophy of sport just were not recognised and considered as bioethical. Thirdly, I will emphasise the issue of the distinction between Ethics and Bioethics of Sport within the Philosophy of Sport. Finally, I will consider some prospects regarding the future of the bioethics of sport.